Changing values in heritage: shifts from the tangible to intangible in urban historic environments bo-kaap as case study - Shem-Tov, Tamar (School of Architecture, Planning and Geomatics, 2021)
This study explores the emergence of changing values associated with heritage in postapartheid South Africa, expressed as a shift from tangible to intangible heritage values. Central to the study is an understanding of the evolutionary construction of changing values in a rooted heritage community within the urban historic environment of Bo-Kaap, the oldest residential suburb of Cape Town. Exploring changing values in Bo-Kaap, where tangible and intangible heritage intersect in the contemporary moment, showcases how heritage ably and fluidly adapts and transforms as an ever-shifting cultural process, and forges new, or altered, modes of identity construction. Bo-Kaap, as the case study, is a significant historic urban environment of Cape Town's central city with a vibrant community having cultural rootedness in place, in slave ancestral heritage, and existing living heritage deserving of protection. It is examined against a backdrop of the localised political, governance and civic agency milieu. The study follows the narrative of Bo-Kaap from its origins as a residential quarter of the early Cape colonial settlement, through the mid twentieth century when Bo-Kaap became largely fashioned and formed into an ethnically defined 'Malay' quarter, conforming to essentialised notions of race and ethnicity dominant in nationalist ideology, through the apartheid regime and the penetrating effects of Group Areas on the social and physical fabric of the area, until the present day where we are witness to a sea-change in outlook of the public on the very meaning and purpose of heritage. Heritage claims and heritage activism entered the realm of active public discourse in 2019 in response to free-market developmental pressures in Bo-Kaap, with inflections of social justice touching the edges of the heritage debate, and invited a broadening of the outermost limits of heritage discourse. Integral to this story is how heritage systems have been shaped by the past and colonial histories, new systems of governance post 1994, and a culture of intensifying identity politics. Following the arc of time illuminates the complex interrelatedness of heritage values with social, historical, and political trajectories, and aims to examine just how dynamically heritage values arise, merge and shift within the inter-relational temporal space; what activates them, who activates them, and to what end; and how they have entered into a space of heritage activism and public discourse. I suggest that this present change in discourse and the display of emerging sets of heritage values requires a highly critical reflexivity on the part of heritage structures and the profession, to look at what these changes mean for heritage praxis and governance and, more importantly, how to advance the relevance of heritage to a sector of South African society advocating for a decolonised heritage value framework.